Optimization of parameters of the reference frequency source with a composite resonator-thermostat - I. V. Khomenko; A. V. Kosykh; E. Yu. Kompanеts (Омский научный вестник)
A promising design of a thermostated quartz oscillator with a resonator-thermostat is considered. In order to study the effect of replacing the material of the microplate in the resonator-thermostat on the operation of the generator, the processes of establishing a stationary temperature regime after switching on are investigated. The material of the new microplate corresponds to the technology of lowtemperature co-fired ceramics. An unacceptable change in the nature of the establishment of a stationary regime has been detected. To solve the problem found, the design change is proposed.